Efektivitas Virtual Reality (VR) dalam Peningkatan Kualitas Hidup Lansia - Maulani, Zulviana Nurahma; Aryanti, Khofifah; Lestari, Novi Arsita Puji; Silitonga, Parulian Geofany; Cahyaningsih, Rossa Berlian; Sunari, Tia Bella; Pradana, Anung Ahadi (Jurnal Kesehatan Holistic, 2021)
The growth of older adults population is predicted to increase rapidly in the future, especially in developing countries including Indonesia. The increasing number of older adults every year can increase their dependency on productive groups, especially in older adults who experience cognitive and motor disorders. The use of assistive tools in older adults can be one of the right methods in preventing dependence and improving the quality of life of older adults. Virtual Reality (VR) is known to be one of the assistive tools that have the potential to help and have a positive impact on older adults with cognitive and motor disorders. The search method in this article uses a simple literature review using several databases and search websites including PubMed, Google Scholar, ACM Dl digital library, and ScienceDirect. The results of the analysis of 11 selected articles stated that the use of VR can help improve cognitive function, motor function, and can reduce the risk of falling in older adults so that in the end it has a positive effect on the quality of life of older adults. Given the high costs involved in implementing VR technology, the use of this assistive tool can be one of the programs that can be used in the management of care by health workers in the future.